Vesicular disease: diagnosis and treatment (Colombia Medica, 1988)
One hundred and fifty-three gall bladder disease (GBD) cases operated on at the Hospital Universitario del Valle, Cali, Colombia, in 1983 were reviewed. Of the patients, 61% were older than 40; the female/male ratio was 5:1. Right upper quadrant pain was the most frequent symptom and sign. Leucocytosis was present in 35% of patients and jaundice in 15%. Due to the high proportion of false positive cases leading to unnecessary GBD exploration with high morbimortality, oral cholecystography was performed in 50% of cases and echography in 26.8%. Different stages of acute cholecystitis were found in 45% of patients. The normal gall bladder was removed in 3% of cases. Acalculous cholecystitis appeared in 9.2% of cases. The most frequently isolated bacteria were E. coli and Klebsiella pneumoniae. Subhepatic drainage was performed in only 5% of cases. Postoperative complications were present in 13% of cases, and the most frequent were: wound infection and unrecognized GBD stones.